Identification of Lithium Plating in Lithium-Ion Batteries using Nonlinear Frequency Response Analysis (NFRA). (10th August 2018) - Harting, Nina; Wolff, Nicolas; Krewer, Ulrike
Abstract: Nonlinear Frequency Response Analysis (NFRA) is a novel dynamic analysis method for Lithium-ion batteries. In contrast to the most commonly applied Electrochemical Impedance Spectroscopy (EIS), NFRA is not limited to the linear response of the system, as it uses higher sinusoidal excitation currents I A C of approximately 1.5 C. Higher harmonic response signals Y n with n2 are analysed. Thereby, additional dynamic information about the system is accessible. Here, the authors evaluate the potential of NFRA to detect the safety critical ageing process of Lithium plating. NFRA results are analysed and compared to EIS for cells aged at − 10 ∘ C with plating occurence and for cells without plating aged at 25 ∘ C. A proof of concept for detection of Lithium plating with NFRA is presented. The third harmonic, Y 3, is strongly sensitive to plated Lithium at time constants characteristic for electrochemical reactions for the analysed cells. Here, Lithium plating causes an increase of charge transfer resistance between the anode and the electrolyte, which affects the nonlinear behaviour. Ex-situ analysis validated that plating occurs only for the cells aged at − 10 ∘ C, but not for the cells aged at 25 ∘ C. Further, it is presented that Y 1, analysed with EIS, is not sufficient for the diagnosis of this ageing process. Therefore, NFRA is suggested as a new, reliable method for the identification of Lithium plating in Lithium-ion batteries.